2020
DOI: 10.1002/btpr.3069
|View full text |Cite
|
Sign up to set email alerts
|

A functional long‐term 2D serum‐free human hepatic in vitro system for drug evaluation

Abstract: Human in vitro hepatic models generate faster drug toxicity data with higher human predictability compared to animal models. However, for long-term studies, current models require the use of serum and 3D architecture, limiting their utility. Maintaining a functional long-term human in vitro hepatic culture that avoids complex structures and serum would improve the value of such systems for preclinical studies. This would also enable a more straightforward integration with current multi-organ devices to study h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
(263 reference statements)
0
4
0
Order By: Relevance
“…Correspondently, the firing frequencies recorded by MEA analysis demonstrated gradual increases during a similar time period in culture. Our success in the differentiation of the iPSCs into a high level of maturity and function without the need for serum, astrocytes, or conditioned medium is due to our long history of utilizing serum-free, defined systems to culture pure populations of cells, including hepatocytes ( Oleaga et al., 2021 ), cardiac cells ( Das et al., 2004 ; Stancescu et al., 2015 ), motoneurons ( Guo et al., 2010 ), skeletal muscle ( Badu-Mensah et al., 2020 ), as well as combination of the cells in multi-organ systems for up to 28 days ( Oleaga et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondently, the firing frequencies recorded by MEA analysis demonstrated gradual increases during a similar time period in culture. Our success in the differentiation of the iPSCs into a high level of maturity and function without the need for serum, astrocytes, or conditioned medium is due to our long history of utilizing serum-free, defined systems to culture pure populations of cells, including hepatocytes ( Oleaga et al., 2021 ), cardiac cells ( Das et al., 2004 ; Stancescu et al., 2015 ), motoneurons ( Guo et al., 2010 ), skeletal muscle ( Badu-Mensah et al., 2020 ), as well as combination of the cells in multi-organ systems for up to 28 days ( Oleaga et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These human-derived liver cells have been established to maintain viability, CYP1A1 and 3A4 activity, and albumin secretion for up to 28 days in serum-free medium in a single organ platform and in a multi-organ system under flow. The previous characterization of this 2D liver cell module established that the primary hepatocytes maintain a characteristic morphology, express key markers (MRP1, actin and albumin) and produce urea and albumin and maintain CYP P450 activity for 28 days 26 . Further, these cells also maintain their phenotype and CYP 1A1 and 3A4 activity under flow for 28 days in a multi-organ interconnected system 27 , 28 .…”
Section: Resultsmentioning
confidence: 98%
“…However, the scarcity of liver tissues for isolating PHHs as well as their phenotypic instability and the short lifespan limit their application for DILI evaluations, particularly for long-term studies, or for reproducing the pharmacokinetics of drug exposure. Recently, different strategies for maintaining hepatocyte function in vitro for a long time, such as the use of a small-molecule combination [ 117 ] or their culture in serum-free conditions [ 86 ], have been proposed for keeping the PHH phenotype up to 4 weeks, which would allow their use for long-term hepatotoxicity assessments. In fact, PHHs cultured under serum-free conditions have been used for studying the acute (48 h) and chronic (23 days) toxicity of six drugs, validating the sensitivity of the system for long-term assessments.…”
Section: In Vitro Cell Models For Chronic Hepatotoxicitymentioning
confidence: 99%
“…In fact, PHHs cultured under serum-free conditions have been used for studying the acute (48 h) and chronic (23 days) toxicity of six drugs, validating the sensitivity of the system for long-term assessments. Significant changes in albumin secretion and CYP3A4 activity were found after 4 weeks treatment with atorvastatin or acetaminophen (APAP), even at subcytotoxic concentrations, indicating their suitability for long-term studies [ 86 ]. This is important because, although APAP is known to induce acute DILI, this study demonstrated that PHHs, under the described conditions, can be exposed to drugs for long periods (4 weeks), and, in order to simulate in vivo drug metabolism and hepatotoxicity, in vitro models should keep morphology and identity, including drug response.…”
Section: In Vitro Cell Models For Chronic Hepatotoxicitymentioning
confidence: 99%